The Main Areas of Development of the Non-Oil Sector in the Republic of Azerbaijan - ABDULLAYEV, Kamran; GULIYEV, Fikrat; TEYMUROVA, Gunay; ALLAHVERDIYEVA, Muslumat; BAGIROVA, Nigar (Theoretical and Practical Research in Economic Fields, 2024)
The Republic of Azerbaijan, historically reliant on its oil sector for economic growth, now seeks to diversify its economy to ensure sustainable development. This study aims to pinpoint key opportunities for bolstering Azerbaijan’s non-oil sectors. Through analysis, historical review, and forecasting, it becomes evident that Azerbaijani authorities are increasingly prioritizing economic diversification. This shift is seen as essential for fostering economic resilience, generating employment opportunities, and mitigating vulnerability to fluctuating energy prices. Government initiatives play a pivotal role in supporting non-oil sectors, with significant investments channeled through state programs aimed at enhancing sectoral attractiveness and competitiveness. Efforts to improve infrastructure, particularly through projects like the Zangezur and Middle Corridor developments, are crucial for expanding transport and transit capacities, thereby facilitating economic diversification. Public-private partnerships (PPPs) are also highlighted as effective mechanisms for nurturing specific industries and creating robust infrastructure to benefit both economic development and the populace at large. Analysis reveals promising trends within Azerbaijan’s non-oil sectors, underscoring ongoing advancements and successes. Ultimately, the findings of this study provide valuable insights for shaping national economic policies, particularly in fortifying Azerbaijan’s non-oil economy. By leveraging these insights, policymakers can strategically steer the country towards a more diversified economic landscape, reducing dependence on oil revenues and fostering sustainable growth across various sectors.